An inkjet printing ink for synthesizing perovskite quantum dots using an environmentally friendly solvent, a film thereof, and applications thereof
By using ternary solvent systems of ethyl acetate, butyl benzoate and ortho-dichlorobenzene in perovskite quantum dot ink, the problems of stability and printability of perovskite quantum dot ink are solved, and a uniform surface, high-quality perovskite film formation is achieved, reducing production costs.
Patent Information
- Application Number
- CN202310873697.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-07-17
AI Technical Summary
The prior art is difficult to prepare perovskite quantum dot ink with excellent performance, stable and printable performance and high-quality perovskite films, and traditional solvents are sensitive to perovskite quantum dots, which easily leads to agglomeration and precipitation.
Ethyl acetate (EA) is used as the main solvent, combined with butyl benzoate (BB) and ortho-dichlorobenzene (ODCB) as co-solvents, a ternary solvent system perovskite quantum dot ink was prepared. By adjusting the viscosity, boiling point and surface tension of the solvent, the "coffee ring" effect of the film is suppressed and uniform film formation is achieved.
It significantly alleviates the aggregation of solutes, inhibits the "coffee ring" effect of the film in printing, and realizes a uniform surface and low roughness inkjet printing film. It has a simple process and is suitable for large-area printing, reducing the cost of device production.
Smart Images

Figure CN117025028B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of luminescent inks, and in particular to an inkjet printing ink for synthesizing perovskite quantum dots using an environmentally friendly solvent, a film thereof and applications thereof. Background Art
[0002] Perovskite quantum dots are a new type of quantum dot material developed in recent years. Compared with traditional cadmium quantum dots (CdSe, CdS, CdTe, etc.), they have lower toxicity, narrower half-width, higher color purity and fluorescence quantum yield, and their color gamut can be as high as 130%. Among them, inorganic cesium lead halide perovskites (CsPbX3, X=Cl, Br and I) show relatively better photostability, thermal stability and environmental stability, which makes them have low-cost and large-scale commercial manufacturing capabilities. The combination of inkjet printing and perovskite quantum dot materials is expected to realize a new generation of printable, low-cost, high-performance perovskite quantum dot light-emitting diode (QLED) high-definition display devices. However, only a few research works focus on the development of perovskite quantum dot inks and their corresponding printed QLED devices. The main reason is that it is challenging to prepare excellent, stable and printable perovskite quantum dot inks and to inkjet print high-quality perovskite films.
[0003] Invention application CN116285499A discloses a method for preparing a novel functional perovskite quantum dot ink. The perovskite quantum dot material is coated with a stable polymer material PCL to develop a novel stable quantum dot ink suitable for electrofluidic printing. The ink retains the excellent spinnability and mechanical properties of the PCL material and has the photoluminescence and electroluminescence properties of CsPbBr3 quantum dots. The ink can be applied to piezoelectric printing and micro-nano electrofluidic printing to prepare micron or submicron scale micro-patterns. However, the processing method is relatively complicated and the complex additives are likely to have adverse effects on the performance.
[0004] Lead halide perovskite quantum dots are ionic materials that are highly sensitive to polar solvents. Solvents commonly used in inkjet-printed QLEDs and organic light-emitting diodes, such as ethers and halogenated alkanes, are not suitable for perovskite quantum dots, which may induce quantum dot agglomeration and precipitation. In addition, it is difficult to introduce traditionally used additives, such as polymers and surfactants, into perovskite quantum dot inks because these additives may act as quenching centers in the quantum dot film and reduce the efficiency of the QLED. Most importantly, the ideal perovskite quantum dot ink for efficient inkjet-printed QLEDs should have good stability, dispersibility, orthogonality, and printability. Therefore, it has become a daunting task to develop high-quality perovskite quantum dot inks composed of pure organic solvents and without any additives for inkjet-printed QLEDs. Summary of the invention
[0005] The main purpose of the present invention is to prepare inkjet-printed perovskite quantum dot ink based on a perovskite quantum dot solution synthesized by the green solvent ethyl acetate (EA) by adding a co-solvent with matching viscosity, surface tension and polarity, and to verify the feasibility of inkjet printing technology to achieve uniform and smooth perovskite quantum dot films under different ink formulations and on different substrates.
[0006] The purpose of the present invention is to provide a perovskite quantum dot ink formula synthesized by an environmentally friendly solvent for inkjet printing, improve the "coffee ring" effect of the perovskite quantum dot film, and achieve uniform film formation.
[0007] The technical solution of the present invention: The present invention provides an inkjet printing perovskite quantum dot ink formula, and the solvent of the ink includes ethyl acetate (EA), butyl benzoate (BB), and o-dichlorobenzene (ODCB).
[0008] Preparation method of the ink:
[0009] (1) Under the operating environment of a nitrogen glove box, take out a portion of the synthesized perovskite quantum dot solution with EA as the main solvent;
[0010] (2) Mixing with BB and ODCB co-solvents according to the designed volume ratio;
[0011] (3) Preparing a ternary solvent system perovskite quantum dot ink;
[0012] (4) Finally, stir the mixture on a magnetic stirrer at room temperature for 4-5 hours to ensure that the mixed solution is evenly dispersed.
[0013] The ratios of the ternary solvent system are EA:BB:ODCB=5:(1.67~4):(1~2).
[0014] The present invention also provides an inkjet-printed perovskite quantum dot film, which is prepared by using the perovskite quantum dot ink provided above on a hole transport layer.
[0015] The hole transport layer substrates are polyethylene dioxythiophene:poly(styrene sulfonate) (PEDOT:PSS), polyvinyl carbazole:phosphomolybdic acid (PVK:PMA), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]:phosphomolybdic acid (PTAA:PMA).
[0016] The inkjet-printed perovskite quantum dot film comprises: inkjet-printing the perovskite quantum dot ink on the hole transport layer, setting the printing spacing, printing height and driving voltage to 40-50 μm, 800-1200 μm and 16-20 V, and after the inkjet printing is completed, annealing at 40 ° C for 5-10 min to solidify the film, so as to obtain the perovskite quantum dot film.
[0017] The present invention also provides the application of the inkjet printing ink prepared by the above method using environmentally friendly solvent to synthesize perovskite quantum dots, including luminescent films, luminescent devices, photovoltaic devices, detectors, and the like.
[0018] Compared with the prior art, the present invention has the following significant advantages:
[0019] (1) The present invention provides an inkjet printing ink formula for synthesizing perovskite quantum dots using an environmentally friendly solvent. The perovskite quantum dot ink adopts a ternary solvent system, so that the viscosity, boiling point, and surface tension of the solvent form a gradient volatilization during the evaporation process, which better balances the boiling point and surface tension of the mixed solvent, significantly alleviates the aggregation of solutes, inhibits the "coffee ring" effect of the film during printing, and realizes an inkjet printing film with a uniform surface and low roughness.
[0020] (2) The present invention has a simple manufacturing process and is applicable to large-area printing and preparation. Meanwhile, the material cost is low, which is beneficial to reducing the manufacturing cost of the device. In addition, high-resolution nano patterns can be achieved through simple and low-cost inkjet printing technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a droplet morphology of the binary solvent perovskite quantum dot ink of Comparative Examples 1 to 6 of the present invention;
[0022] Figure 2 It is the image of the original CsPbBr3 quantum dot ink under ultraviolet light of the present invention and the image of the ternary solvent CsPbBr3 quantum dot ink of Examples 1 to 3;
[0023] Figure 3 are the PL and absorption spectra of the original CsPbBr3 quantum dot solution of the present invention and the CsPbBr3 quantum dot ink of Example 3;
[0024] Figure 4 It is the in-situ volatilization microscopic image of the ternary solvent system CsPbBr3 quantum dot ink of Examples 1 to 3;
[0025] Figure 5 is a droplet morphology image of the inkjet-printed perovskite quantum dot ink of Examples 3 to 6;
[0026] Figure 6are the droplet contact angles and film morphologies of inkjet-printed perovskite quantum dots of Examples 3 to 6;
[0027] Figure 7 is a morphology image of a film prepared at different printing intervals in Example 6;
[0028] Figure 8 is the UV-Vis absorption spectrum of the PTAA:PMA substrate in Example 6 before and after spin washing with EA, BB, and ODCB solvents;
[0029] Fig. 9 is a schematic diagram of the device structure of the inkjet-printed perovskite quantum dot light-emitting diode prepared in Example 4;
[0030] Fig.10 It is a current density-voltage-brightness characteristic diagram, a current efficiency-voltage curve diagram, and an electroluminescence (EL) spectrum diagram of the inkjet-printed perovskite quantum dot light-emitting diode prepared in Example 4. DETAILED DESCRIPTION
[0031] The objects, advantages and features of the present invention are illustrated and explained by the non-limiting description of the following preferred embodiments. These embodiments are only typical examples of the technical solutions of the present invention. All technical solutions formed by equivalent replacement or equivalent transformation fall within the scope of protection claimed by the present invention. The technical solutions of the present invention are further described below in conjunction with the embodiments. Comparative Example 1
[0032] (1) The synthesized CsPbBr3 quantum dot solution is mixed with an organic solvent, wherein the mixed solvent consists of ethyl acetate and cyclohexylbenzene, wherein the volume ratio of ethyl acetate to cyclohexylbenzene in the mixed solvent is 7:3.
[0033] (2) ITO was selected as the substrate. The substrate was ultrasonically treated in acetone, ethanol, and deionized water for 15 min in sequence. After being blown dry with nitrogen, it was placed in a 120 °C oven for drying. A layer of PEDOT:PSS film was spin-coated on the surface of the cleaned ITO substrate at a speed of 3000 rpm for 60 s, and then annealed at 120 °C for 30 min.
[0034] (3) The CsPbBr3 quantum dot mixed ink was inkjet printed on the PEDOT:PSS substrate. After the inkjet printing was completed, the film was annealed at 40°C for 5-10 min to solidify. Comparative Example 2
[0035] The steps and technical parameters of Comparative Example 2 are basically the same as those of Comparative Example 1, except that the volume ratio of ethyl acetate to cyclohexylbenzene is 5:5. Comparative Example 3
[0036] (1) The synthesized CsPbBr3 quantum dot solution is mixed with an organic solvent, wherein the mixed solvent consists of ethyl acetate and o-dichlorobenzene, wherein the volume ratio of ethyl acetate to o-dichlorobenzene in the mixed solvent is 5:5.
[0037] (2) ITO was selected as the substrate. The substrate was ultrasonically treated in acetone, ethanol, and deionized water for 15 min in sequence. After being blown dry with nitrogen, it was placed in a 120 °C oven for drying. A layer of PEDOT:PSS film was spin-coated on the surface of the cleaned ITO substrate at a speed of 3000 rpm for 60 s, and then annealed at 120 °C for 30 min.
[0038] (3) The CsPbBr3 quantum dot mixed ink was inkjet printed on the PEDOT:PSS substrate. After the inkjet printing was completed, the film was annealed at 40°C for 5-10 min to solidify. Comparative Example 4
[0039] (1) Mixing the synthesized CsPbBr3 quantum dot solution with an organic solvent, wherein the mixed solvent consists of ethyl acetate and butyl benzoate, wherein the volume ratio of ethyl acetate to butyl benzoate in the mixed solvent is 5:5.
[0040] (2) ITO was selected as the substrate. The substrate was ultrasonically treated in acetone, ethanol, and deionized water for 15 min in sequence. After being blown dry with nitrogen, it was placed in a 120 °C oven for drying. A layer of PEDOT:PSS film was spin-coated on the surface of the cleaned ITO substrate at a speed of 3000 rpm for 60 s, and then annealed at 120 °C for 30 min.
[0041] (3) The CsPbBr3 quantum dot mixed ink was inkjet printed on the PEDOT:PSS substrate. After the inkjet printing was completed, the film was annealed at 40°C for 5-10 min to solidify. Comparative Example 5
[0042] The steps and technical parameters of Comparative Example 5 are basically the same as those of Comparative Example 4, except that the volume ratio of ethyl acetate to butyl benzoate is 4:6. Comparative Example 6
[0043] The steps and technical parameters of Comparative Example 6 are basically the same as those of Comparative Example 4, except that the volume ratio of ethyl acetate to butyl benzoate is 6:4.
[0044] The droplet morphology of the binary solvent perovskite quantum dot ink of Comparative Examples 1 to 6 prepared by inkjet printing is as follows: Figure 1As shown. The contact line of the droplet in comparative example 1 is pinned on the substrate, and a coffee ring structure with thick edges and thin middle appears, and the droplet size is small. This is due to the high EA content, low CHB content, reduced solution viscosity, and faster evaporation rate. Capillary flow is proportional to the evaporation rate. A higher evaporation rate will lead to enhanced capillary flow. In order to compensate for the solvent loss caused by the uneven evaporation rate between the center and the edge, a large number of suspended quantum dots in the solvent move from the center to the edge. When they reach the TCL, they are pinned, and the quantum dots quickly gather and deposit at the edge, forming a coffee ring along the edge of the droplet.
[0045] Comparative Example 2 exhibits a multi-ring "coffee ring" phenomenon. This can be explained as follows: During the evaporation and drying process of the droplets, the three-phase contact line is constantly undergoing a pinning and depinning process, and the quantum dots will migrate along the three-phase contact line instead of all gathering in the pinning area. First, the edge of the droplet will be fixed after it falls on the substrate. Due to the different evaporation rates at the center and edge of the droplet, in order to compensate for the solvent loss at the edge, the quantum dots are carried to the edge by the outward capillary flow, forming a coffee ring. Subsequently, the contact line moves with the contraction of the droplet, and depinning and migration occur. At this time, the contact line is not pinned, and there is no capillary flow from the inside to the outside, so the quantum dot particles are not pinned to the edge of the droplet. The quantum dots that first move to the contact line are separated from the solvent and deposited on the PEDOT:PSS layer. Ultimately, the pinning and depinning processes alternate multiple times, forming multiple coffee rings. From Figure 1 It can be seen that after deposition and drying, Comparative Examples 3 and 4 also exhibited different degrees of multi-ring "coffee ring" phenomenon. Comparative Examples 5 and 6 still could not eliminate this phenomenon. Example 1
[0046] (1) The synthesized CsPbBr3 quantum dot solution is mixed with an organic solvent, wherein the mixed solvent consists of ethyl acetate, butyl benzoate and o-dichlorobenzene, wherein the volume ratio of ethyl acetate, butyl benzoate and o-dichlorobenzene in the mixed solvent is 5:4:1.
[0047] (2) ITO was selected as the substrate. The substrate was ultrasonically treated in acetone, ethanol, and deionized water for 15 min in sequence. After being blown dry with nitrogen, it was placed in a 120 °C oven for drying. A layer of PEDOT:PSS film was spin-coated on the surface of the cleaned ITO substrate at a speed of 3000 rpm for 60 s, and then annealed at 120 °C for 30 min.
[0048] (3) The CsPbBr3 quantum dot mixed ink was inkjet printed on the PEDOT:PSS substrate. After the inkjet printing was completed, the film was annealed at 40°C for 5-10 min to solidify. Example 2
[0049] The steps and technical parameters of Example 2 are basically the same as those of Example 1, except that the volume ratio of ethyl acetate, butyl benzoate and o-dichlorobenzene is 5:3:2. Example 3
[0050] The steps and technical parameters of Example 3 are basically the same as those of Example 1, except that the volume ratio of ethyl acetate, butyl benzoate and o-dichlorobenzene is 6:2:2.
[0051] The difference between Examples 1 to 3 and Comparative Example 4 is that o-dichlorobenzene is added to the mixed solvent of Examples 1 to 3 on the basis of ethyl acetate and butyl benzoate to prepare the ternary solvent system CsPbBr3 perovskite quantum dot ink, and the other steps and technical parameters are the same.
[0052] Figure 2 The following are images of the original CsPbBr3 quantum dot ink and the ternary solvent CsPbBr3 quantum dot ink in different proportions under UV light (Examples 1-3). It can be seen that the addition of BB and ODCB does not affect the stability and luminescence of the original perovskite quantum dot solution. At the same time, the PL and absorption spectra of the CsPbBr3 quantum dot ink are compared, as shown in Figure 1. Figure 3 As shown in Figure 2, when BB and ODCB were added to EA, the PL and absorption intensity decreased slightly.
[0053] The ternary solvent inks of Examples 1 to 3 were printed on a PEDOT:PSS substrate, and the microscopic images of the wet and dry films during in-situ evaporation of the droplets were compared. Figure 4 As shown in the figure, during the in-situ volatilization process of the droplets on the substrate, a multi-ring morphology first appeared. Since the evaporation rate at the edge of the droplet was faster than that at the center of the droplet, as the volatilization time increased, the rings gradually merged from the edge to the center, and finally formed a single ring without an obvious coffee ring. Compared with binary solvents, the viscosity, boiling point and surface tension of ternary solvents theoretically form a certain gradient, which helps to prolong the Marangoni flow during the droplet evaporation and drying process, thereby inhibiting the "coffee ring" effect. Example 4
[0054] (1) The synthesized CsPbBr3 quantum dot solution is mixed with an organic solvent, wherein the mixed solvent consists of ethyl acetate, butyl benzoate and o-dichlorobenzene, wherein the volume ratio of ethyl acetate, butyl benzoate and o-dichlorobenzene in the mixed solvent is 6:2:2.
[0055] (2) ITO was selected as the substrate. The substrate was ultrasonically treated in acetone, ethanol, and deionized water for 15 min in sequence. After being blown dry with nitrogen, it was placed in a 120 °C oven for drying. A layer of PEDOT:PSS film was spin-coated on the surface of the cleaned ITO substrate at a speed of 3000 rpm for 60 s, and then annealed at 120 °C for 30 min.
[0056] (3) Further, a hole transport layer PVK:PMA was prepared on PEDOT:PSS by spin coating, and the hole transport layer thickness was 40 nm. The spin coating speed was 2000 rpm, the spin coating time was 60 s, and the layer was annealed at 120 °C for 5 min.
[0057] (4) The CsPbBr3 quantum dot mixed ink was inkjet printed on the cross-linked PVK:PMA substrate. After the inkjet printing was completed, the film was annealed at 40 °C for 5-10 min to solidify. Example 5
[0058] The steps and technical parameters of Example 5 are basically the same as those of Example 4, except that the hole transport layer PTAA is prepared on PEDOT:PSS by spin coating, the spin coating speed is 3000 rpm, the spin coating time is 60 s, and annealing is performed at 130°C for 10 min. Example 6
[0059] The steps and technical parameters of Example 6 are basically the same as those of Example 4, except that the hole transport layer PTAA:PMA is prepared on PEDOT:PSS by spin coating at a spin coating speed of 2000 rpm for 60 s and annealing at 130°C for 10 min.
[0060] The morphology of a single droplet of inkjet printing in Examples 3 to 6 is as follows: Figure 5 As shown. On the PEDOT:PSS and PVK:PMA substrates, the droplets did not show obvious coffee rings. The droplets on the PVK:PMA substrate spread more evenly, and the droplet morphology was relatively flat and larger in size. On the PTAA and PTAA:PMA substrates, the droplets showed a coffee ring morphology with thick edges and thin middles. This may be because PVK:PMA is a cross-linked HTL, which effectively prevents the quantum dot ink from dissolving the underlying transport layer; while the uncross-linked PTAA and PTAA:PMA, due to the interlayer solubility of quantum dots and the above-mentioned transport layer, may cause solute pinning at the TCL; and the solvent evaporates faster at the edge, affecting the balance of capillary flow and Marangoni flow, and finally forming a coffee ring on the substrate.
[0061] The film-forming properties of the ternary solvent perovskite quantum dot inks printed by inkjet printing in Examples 3 to 6 were further analyzed, and the contact angles of the droplets on four different substrates were 11.38°, 11.16°, 11.32°, and 11.46°, respectively. Figure 6 As shown, Example 3 prints a film on a PEDOT:PSS substrate. The perovskite QD film printed in the wet film state is discontinuous and has large-sized holes. In the drying process, the slow evaporation rate of the droplets leads to poor film uniformity and rough surface morphology. Example 4 prints a film on a PVK:PMA substrate. The film is continuous and flat in the wet film state, and the film in the dry state is flatter and smoother than the film printed on the PEDOT:PSS substrate; Example 5 prints a film on a PTAA substrate. The film also shows a continuous and flat film in the wet film state, but during the evaporation process, as the film dries from the edge to the center, black impurities gradually precipitate in the center, and because a single droplet has a more obvious coffee ring, the edge of the printed film is thicker; Example 6 prints a film on a PTAA:PMA substrate with a printing spacing of 50 μm. In the wet film state, black particles are attached to the surface of the film. In the dry state, the uneven thickness of the film layer leads to obvious stripes.
[0062] The printing spacing of the film on the PTAA:PMA substrate of Example 6 was further adjusted, and the film was printed at spacings of 90 μm, 70 μm, and 55 μm, respectively. When the printing spacing was 90 μm and 70 μm, the droplet spacing was too large to form a continuous film, and there were many holes and coffee rings, indicating that the film thickness was obviously uneven; when the printing spacing was 55 μm, the film was close to continuous, but there was still uneven thickness, and black impurities were distributed in the film, such as Figure 7 shown.
[0063] Since the film thickness was uneven when the ternary solvent perovskite quantum dot ink was inkjet printed on the PTAA:PMA substrate in Example 6, the solvent resistance test of the PTAA:PMA film was carried out. Figure 8 UV-Vis absorption spectra of the films before and after spin washing with EA, BB, and ODCB solvents. Figure 8 Figure 1 is the absorption intensity of the PTAA:PMA film before spin washing; the absorption intensity of the PTAA:PMA substrate is slightly reduced after being spin washed with the green solvent EA. Figure 8 As shown in 2; and after washing with organic solvents BB and ODCB, the absorption intensity decreased significantly, as shown in Figure 8As shown in Figures 3 and 4, it is shown that the PTAA:PMA substrate does not have good cross-linking ability and excellent solvent resistance, resulting in interfacial miscibility between film layers. In addition, although the contact angle of the droplet on the PTAA:PMA substrate is 11.46°, which has good wetting ability, the contact angle is larger than that of other substrates, and the droplet does not diffuse sufficiently during evaporation. Under the influence of the coffee ring, the edge of the droplet is more likely to be pinned on the substrate, eventually forming a striped film with obvious uneven thickness. Example 7
[0064] The inkjet-printed perovskite quantum dot light-emitting diode prepared in Example 4 was used.
[0065] (1) The ITO anode was ultrasonically cleaned with acetone, ethanol, and deionized water in turn, and the surface was dried with a nitrogen stream and placed in an oven at 120 °C for drying. After the ITO anode was cooled, it was treated with UV ozone for 20 min. Then, the PEDOT:PSS solution was spin-coated on the ITO surface and annealed on a hot plate at 120 °C for 30 min to obtain a hole injection layer with a thickness of 30 nm.
[0066] (2) The ITO spin-coated with PEDOT:PSS was placed in a nitrogen glove box. A hole transport layer PVK:PMA was prepared on the PEDOT:PSS at a spin coating speed of 2000 rpm and a spin coating time of 60 s. After annealing at 120 °C for 5 min, a hole transport layer with a thickness of 40 nm was obtained.
[0067] (3) The perovskite quantum dot ink was inkjet printed on the hole transport layer with the printing spacing, printing height and driving voltage set to 50 μm, 1200 μm and 20 V, and then placed on a hot plate at 40 °C for annealing for 5-10 min.
[0068] (4) Place the above-mentioned ITO glass with perovskite quantum dots printed on it in a vacuum evaporation device and wait until the vacuum degree reaches 2×10 -4 When the surface temperature is 4000 nm, TPBi, LiF and Al are sequentially evaporated on the surface with thicknesses of 40 nm, 1 nm and 100 nm, respectively.
[0069] Fig. 9 This is a schematic diagram of the device structure of an inkjet-printed perovskite quantum dot light-emitting diode constructed in Example 7 of the present invention, wherein the anode is ITO conductive glass, the hole injection layer is poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), the hole transport layer is PVK:PMA, the perovskite quantum dot layer is CsPbBr3, the electron transport layer is tri(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), the electron injection layer is lithium fluoride (LiF), and the cathode is metallic aluminum (Al).
[0070] Fig.10 The current density-voltage-brightness characteristic diagram, current efficiency-voltage curve diagram, and electroluminescence (EL) spectrum diagram of the inkjet-printed perovskite quantum dot light-emitting diode of the present invention are shown in FIG. Fig.10 It can be seen that the turn-on voltage of the inkjet-printed blue light perovskite quantum dot light-emitting diode is about 3.2 V, the maximum current efficiency is 0.4 cd / A, and the emission peak of the EL spectrum is at 456 nm.
[0071] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. An environmentally friendly solvent-synthesized perovskite quantum dot inkjet printing ink, characterized in that: The ink includes a CsPbBr3 quantum dot solution and an organic solvent, wherein the organic solvent is a ternary mixed solvent of ethyl acetate, butyl benzoate, and o-dichlorobenzene; the volume ratio of the organic solvent is ethyl acetate: butyl benzoate: o-dichlorobenzene = 5: (1.67~4): (1~2).
2. The inkjet printing ink for synthesizing perovskite quantum dots using environmentally friendly solvents according to claim 1, characterized in that: The preparation method of the ink comprises the following steps: (1) Under the operating environment of a nitrogen glove box, take out a portion of the synthesized perovskite quantum dot solution with ethyl acetate as the main solvent; (2) mixing with butyl benzoate and o-dichlorobenzene co-solvent respectively according to the designed volume ratio; (3) Preparing a ternary solvent system perovskite quantum dot ink; (4) Finally, stir the mixture on a magnetic stirrer at room temperature for 4-5 hours to ensure that the mixed solution is evenly dispersed.
3. An inkjet printed perovskite quantum dot film, characterized in that: The film is obtained by printing the inkjet printing ink of synthesizing perovskite quantum dots with the environmentally friendly solvent in claim 1 or 2 on the hole transport layer, wherein the hole transport layer is selected from polyethylene dioxythiophene:poly(styrene sulfonate) and polyvinyl carbazole:phosphomolybdic acid (PVK:PMA).
4. The inkjet-printed perovskite quantum dot film according to claim 3, characterized in that: The printing parameters are as follows: the printing spacing, printing height and driving voltage are set to 40-50 μm, 800-1200 μm and 16-20 V. After the inkjet printing is completed, the film is solidified by annealing at 40 °C for 5-10 min to obtain a perovskite quantum dot film.
5. An application of an inkjet printing ink synthesized from an environmentally friendly solvent for perovskite quantum dots, characterized in that: The inkjet printing ink of perovskite quantum dots is synthesized using the environmentally friendly solvent described in claims 1-2, and is applied to light-emitting films, light-emitting devices, photovoltaic devices, and detectors.
Citation Information
Patent Citations
Preparation method of novel functional perovskite quantum dot ink
CN116285499A
No-annealing perovskite type solar cell and preparing method thereof
CN104993060A
Composition for printed electronic component, preparation method therefor, and uses thereof
CN109790406A